Analysis of high-dose tamoxifen therapy efficiency in complex treatment of patients with stage III-IV non-small cell lung cancer - A. I. Shevchenko; A. V. Kadzhoyan (Zaporožskij Medicinskij Žurnal)
With the help of immunohistochemcial methods the frequency of estrogen and progesteron expression in tumor tissue of 30 patients with non-small cell lung cancer was analysed, positive result took place in 1 patient (3%). Assessment of effi ciency of high dose tamoxifenotherapy in combined treatment was performed in 45 patients with III-IV stages of non-small cell lung cancer (control group – 39 patients received chemotherapy only); the results obtained were signifi cantly better in achieving of partial regression and stabilization of the disease in the study group.